Effects of thiamethoxam insecticide on sugarcane plant growth under chemical ripening at early and late harvest - Silva, Deise de Paula; Viveiros, Josiane; Jacomassi, Lucas Moraes; Pacola, Marcela; Momesso, Letusa; de Siqueira, Gabriela Ferraz; Martello, Jorge Martinelli; Foltran, Rodrigo; Soratto, Rogério Peres; Dinardo-Miranda, Leila Luci; Crusciol, Carlos Alexandre Costa (Frontiers in Plant Science, 2025)
Chemical ripeners are applied to ensure the quality of the final product in sugarcane production, especially under unfavorable conditions for sucrose accumulation. In addition, bioactivators such as the insecticide thiamethoxam can stimulate plant development. Thus, the application of thiamethoxam to sugarcane regrowth associated with ripener may have phytotonic effects and improve sugarcane quality and yield. The aim of this study was to understand the effects of thiamethoxam foliar application to sugarcane ratoon treated with trinexapac-ethyl as a ripener. Four management strategies (treatments) were introduced and tested in six field experiments conducted across the early and late harvest seasons: no chemical application (control), application of 250 g a.i ha-1 trinexapac-ethyl (0.4 L ha-1 of commercial product) as a ripener, application of thiamethoxam 100 g a.i ha-1 (0.4 kg ha-1 of commercial product) as a bioactivator, and application of ripener and bioactivator. Thiamethoxam application increased stalk yield by 14 Mg ha-1 compared with the control, and joint application with ripener increased sugar yield by up to 3 Mg ha-1 due to an increase in total recoverable sugar (TRS) of up to 11% compared with the control (139.9 kg Mg-1). The increases in biomass in response to thiamethoxam application increased potential energy production (MWh) by 16.8% compared with the treatments without insecticide. The integration of thiamethoxam into sugarcane management enhanced yield, biomass, and energy-related traits without compromising technological quality. When combined with trinexapac-ethyl, it increased sugar yield per hectare. These benefits point to improved land-use efficiency. However, given its classification as a neonicotinoid, further studies are needed to assess long-term safety. Such research is key to aligning productivity with sustainability in sugarcane systems.